2018
DOI: 10.1038/s41394-018-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

Weaning from long-term mechanical ventilation utilizing closed-loop ventilation mode (IntelliVent®-ASV®) in a patient with spinal cord injury

Abstract: IntroductionCervical spinal cord injury with the C3 neurological level may cause respiratory failure and require long-term mechanical ventilation. Conventional weaning of spontaneous breathing trials is difficult to perform outside of intensive care or spinal cord units.Case presentationAn 80-year-old man presented with total tetraplegia and restrictive respiratory failure that required assisted ventilation after a falling accident. Cervical spine magnetic resonance imaging showed cervical cord compression tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Different from common ventilated patients who developed ventilator-induced diaphragm dysfunction and lead to weaning difficulties, SCI patients mainly suffered from motor impairment and prolonged mechanical ventilation further impaired diaphragm function. Shimizu et al reported a case where a closed-loop ventilation mode helped weaning from mechanical ventilation in an SCI patient [11]. However, it was a choice due to shortness in medical staffs.…”
Section: Discussionmentioning
confidence: 99%
“…Different from common ventilated patients who developed ventilator-induced diaphragm dysfunction and lead to weaning difficulties, SCI patients mainly suffered from motor impairment and prolonged mechanical ventilation further impaired diaphragm function. Shimizu et al reported a case where a closed-loop ventilation mode helped weaning from mechanical ventilation in an SCI patient [11]. However, it was a choice due to shortness in medical staffs.…”
Section: Discussionmentioning
confidence: 99%
“…INTELLiVENT-ASV has been shown to be safe and sometimes more efficient for weaning cardiac-surgery patients from mechanical ventilation [31 ▪ ,32]. It was also used to wean patients with spinal-cord injury [56].…”
Section: Weaningmentioning
confidence: 99%